Hubungan antara Terpaan Pesan @gerakanbds dengan Perubahan Sikap Followers Mengenai Isu Palestina - 1008002114, Aisya Hatami; Dadi Ahmadi (Bandung Conference Series: Journalism, 2025)
Abstract. Social media plays an important role in distributing information in the form of facts or opinions on Palestinian humanitarian issues over the past year. The @gerakanbds account is one of the accounts on Instagram that actively spreads messages containing facts as well as calls for the public to participate in helping the Palestinian cause. The urgency of this research is based on the emergence phenomenon of organizations that actively use Instagram in disseminating information about boycotts, divestments, and sanctions movements at a time when information is still biased in conventional media. This research aims to examine the significance of the correlation between exposure to @gerakanbds account messages and changes in followers' attitudes regarding Palestinian humanitarian issues. This study uses a quantitative method with a correlational approach. The selected population is accounts that are Instagram followers @gerakanbds as many as 92.6 thousand and the sample drawing using the slovin formula was obtained with a sample size of 100 respondents. The Uses and Effect theory is the basis of the theory with the assumption that messages conveyed through the media can have a certain effect on the recipient of the message. The data of this study was collected through the distribution of questionnaires and conducting Rank Spearman tests to analyze the relationship between the two research variables. The results of the study showed that there was a significant and positive relationship between exposure to @gerakanbds Instagram account messages and changes in followers' attitudes, namely in the form of a tendency to act (conation) in the BDS movement in real terms. Abstrak. Media sosial memegang peran penting dalam menyalurkan informasi berupa fakta ataupun opini mengenai isu kemanusiaan Palestina selama setahun terakhir. Akun @gerakanbds menjadi salah satu akun di Instagram yang secara aktif menyebarkan pesan berisi fakta juga seruan yang mengajak khalayak untuk turut serta dalam membantu perjuangan warga Palestina. Urgensi penelitian ini didasarkan pada fenomena kemunculan organisasi yang aktif memanfaatkan Instagram dalam menyebarkan informasi tentang gerakan boikot, divestasi, dan sanksi di saat masih biasnya informasi di media konvensional. Penelitian yang dilakukan ini bertujuan untuk mengkaji signifikansi korelasi terpaan pesan akun @gerakanbds dengan perubahan sikap followers mengenai isu kemanusiaan Palestina. Penelitian ini menggunakan metode kuantitatif dengan pendekatan korelasional. Populasi yang dipilih adalah akun yang merupakan followers Instagram @gerakanbds sebanyak 92,6 ribu dan penarikan sampel menggunakan rumus slovin diperoleh ukuran sampel sebesar 100 responden. Teori Uses and Effect menjadi landasan teori dengan asumsi pesan yang disampaikan melalui media dapat memberikan efek tertentu bagi penerima pesan. Data penelitian ini dikumpulkan melalui penyebaran kuesioner dan melakukan pengujian Rank Spearman untuk menganalisis hubungan yang terdapat antara kedua variabel penelitian. Hasil penelitian menunjukkan terdapat hubungan signifikan dan positif antara terpaan pesan akun Instagram @gerakanbds dengan perubahan sikap followers yaitu berupa kecenderungan bertindak (konasi) dalam gerakan BDS secara nyata.